miR-185-5p regulates the proliferation and differentiation of neural stem/progenitor cells - Feng, Xuanran; Du, Xue; Yang, Xiaoyu; Chen, Changqi; Liang, Zhanping; Xu, Xiaonan; Wang, Yi; Zheng, Jialin C.; Xia, Xiaohuan; Liu, Jianhui (Frontiers in Cell and Developmental Biology, 2024)
BackgroundMicroRNAs (miRNAs) have emerged as an essential regulator of the cell fate commitment of neural stem/progenitor cells (NPCs), although the impacts of certain miRNAs on NPCs remain vague. The aim of this study is to investigate the regulatory effects of miR-185-5p on the cell fate commitment of NPCs.MethodsWe investigated the impact of miR-185-5p on the proliferation and differentiation capacities of primary NPCs by manipulating the expression of miR-185-5p using specific mimics and inhibitors. The effects of miR-185-5p on NPCs was confirmed in vivo through stereotactic injection of miR-185-5p antagonists to the brains of mice at postnatal day 1 (P1).ResultsThe expression levels of miR-185-5p kept increasing in the differentiation process of NPCs in vivo and in vitro. Perturbation of miR-185-5p’s function showed that miR-185-5p inhibited NPCs’ proliferation and promoted embryonic NPCs to differentiate more favorably to the glial lineage. We then validated the anti-proliferation and pro-glial roles of miR-185-5p using NPCs isolated from P1 mouse brains. In vivo study further showed enlarged NPCs pools and inhibited gliogenesis in the brains of P1 mice after animals received antagomir-185-5p.ConclusionOur study suggests miR-185-5p as an important regulator for the proliferation and glial fate commitment of NPCs.